2012
DOI: 10.1186/1742-4755-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Home birth and barriers to referring women with obstetric complications to hospitals: a mixed-methods study in Zahedan, southeastern Iran

Abstract: BackgroundOne factor that contributes to high maternal mortality in developing countries is the delayed use of Emergency Obstetric-Care (EmOC) facilities. The objective of this study was to determine the factors that hinder midwives and parturient women from using hospitals when complications occur during home birth in Sistan and Baluchestan province, Iran, where 23% of all deliveries take place in non- hospital settings.MethodsIn the study and data management, a mixed-methods approach was used. In the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 35 publications
(48 reference statements)
5
40
2
2
Order By: Relevance
“…The possible explanation might be the fact that mothers in these countries had better educational status (since only 17.6% was illiterate) and better ANC service utilization (since more than 95% had ANC follow up). The finding of this study is lower than WHO recommendation of every pregnancy should be assisted by skill attendance [11]% yet better than Kenya, institutional delivery is 38% [15], the national prevalence [3] and a study in Amhara region, Sekela [16] and Dodota district [18]. This might be due to time gap, increased opportunity for education and difference in place of residence.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The possible explanation might be the fact that mothers in these countries had better educational status (since only 17.6% was illiterate) and better ANC service utilization (since more than 95% had ANC follow up). The finding of this study is lower than WHO recommendation of every pregnancy should be assisted by skill attendance [11]% yet better than Kenya, institutional delivery is 38% [15], the national prevalence [3] and a study in Amhara region, Sekela [16] and Dodota district [18]. This might be due to time gap, increased opportunity for education and difference in place of residence.…”
Section: Discussioncontrasting
confidence: 46%
“…World Health Organizations (WHO) strongly advocates skilled care for every birth to reduce the global burden of 536, 000 maternal deaths every year [11,12]. A community-based cross-sectional study conducted in Nepal showed that out of the total participants, 77.3% had institutional delivery [13].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, having some focused interest in the form of a question is necessary for research design (5) that can be stated as a research aim (7); and although it facilitates the development of research plan, the fact is that the primary question may change. During this process the researcher may find far more interesting things than he or she at first thought (5); as we found during the study and published them within different articles (3,4).…”
Section: Dear Editormentioning
confidence: 72%
“…In spite of geographical and drive-time accessibility of these hospitals, about 10% -12% of local women still choose to deliver their babies at home (3,4). Therefore, the main question is not about maternal mortality rate or the impact of childbirth place on maternal death, but about the use of available services.…”
Section: Dear Editormentioning
confidence: 99%
“…17,18 Di Iran, kaum perempuan percaya bahwa lebih baik meninggal ketika melahirkan di rumah daripada harus bersalin pada bidan ataupun di rumah sakit. 19 Persepsi seperti itu dipengaruhi oleh tingkat pendidikan, budaya , dan kepercayaan serta tingkat ekonomi masyarakat. Di Israel, pada kajian selama sepuluh tahun, ditemukan bahwa masyarakat perdesaan tidak sepenuhnya menggunakan pengobatan medis konvensional untuk mengatasi masalah kesehatan, mereka juga menggunakan berbagai pengobatan alternatif yang membudaya di dalam masyarakat.…”
Section: Pembahasanunclassified